PANDANGAN PENDIDIKAN ISLAM IBNU KHALDUN DAN IMPLEMENTASI KETELADANANNYA PADA PESERTA DIDIK ERA 4.0 - Enik Nur Faizah (Bajang Institute, 2022)
The current view of Islamic education, of course, cannot be separated from the thoughts of previous Islamic education philosophers. Quite a number of Islamic education figures in the classical era contributed their thoughts to the field of education, one of which was about Islamic education and their own examples. In this case the writer takes one of the figures and tries to describe the viewpoint of Islamic education according to him, namely, Ibn Khaldun. Era 4.0, where everything is technology-based can have a good and bad impact on education. The purpose of this paper is to find out the paradigm of Ibn Khaldun's Islamic education, Islamic education in era 4.0 students, and the implementation of Ibn Khaldun's example for era 4.0 students..